Identification of a novel p52-regulated long noncoding RNA in multiple myeloma - Ang, Daniel Aron (Nanyang Technological University, 2020)
Multiple myeloma (MM) is a monoclonal plasma cell neoplasm accounting for 20 % of all blood-associated cancers. Mutations in factors of the non-canonical NF-kB (ncNF-kB) pathway have been associated with MM. Here we show that MM mutant cell lines display constitutive ncNF-kB pathway activation and the role p52 has in cell survival. We then screened for p52 DNA binding targets and target genes through ChIP-Seq and RNA-Seq respectively. We also looked at the enhancer landscape via ChIP-seq profiling of histone H3K27ac marks in a mutant MM cell line. A novel p52 target long intergenic non-coding RNA LINC02362 was identified to be vital for survival in mutant MM cell lines. We also highlighted the differences in enhancer marks in the vicinity of LINC02362 in MM tumours. Together, it provides further insights into potential therapeutic regions for MM which are under the regulation of the ncNF-kB pathway. Finally we explored the idea of using enhancer marks, together with transcription factor binding sites such as p52, to identify prognostic or biomarkers for MM.